Life events and their subjective appraisal by children and adolescents in clinical high-risk states of psychosis: a cross-sectional comparison with inpatients with non-psychotic disorders and community subjects. - Kullmann, Celina; Michel, Chantal; Walger, Petra; Franscini, Maurizia; Traber-Walker, Nina; Schimmelmann, Benno G.; Flückiger, Rahel; Reissner, Volker; Schultze-Lutter, Frauke (European Child & Adolescent Psychiatry, 2026)
While childhood trauma and neglect are generally found to be increased in clinical high-risk of psychosis (CHR-P), findings on life events (LEs) are so far inconclusive, with some indication of a stress sensitization effect in CHR-P, leading to generally higher stress appraisals of LEs, and a LE-reducing effect of negative symptoms. Thus, we studied 50 LEs and their appraisals as assessed with the Munich Life Event Scale in CHR-P patients according to ultra-high risk and basic symptom criteria and age- and sex-matched clinical inpatient (ClinS) and healthy controls (GPS; each n = 112, age 8–17 yrs., 57.1% female). LEs, particularly those of interpersonal nature, were increased in CHR-P compared to GPS but not ClinS, and their number and presence was positively related to subjective negative symptoms. Furthermore, appraisals rarely and only unsystematically differed between groups but correlated significantly in most cases with a more negative appraisal being related to a higher stress appraisal. Thus, there was no indication of a significant stress sensitization effect in CHR-P. Rather, the increased number of LEs, in particular interpersonal ones, likely increases the overall load of stress in terms of a stress accumulation and decreases the size of the supportive social network as well as increases negative symptoms. Thus, early interventions in CHR-P should also include improving strategies to deal with LEs, particularly those of interpersonal nature, to improve resilience and reduce burden of non-normative LEs.